GENETIC DIVERGENCE AMONG Passiflora cristalina Vanderpl & Zappi. GENOTYPES BASED ON FLOWER AND FRUIT CHARACTERISTICS - SILVEIRA,GREICIELE FARIAS DA (2016)
ABSTRACT This study aimed to evaluate the genetic divergence among Passiflora cristalina genotypes and quantify the relative contribution of 30 flower and fruit characteristics, seeking to support the preservation and characterization of genetic resources of the species for preservation and use in future breeding programs. We evaluated 150 fruit and 150 flowers collected in 15 genotypes with naturally occurring in the municipality of Alta Floresta, MT. The characterization of genotypes was performed through 30 morphological characteristics of flowers and fruits, 21 of these for flower and 9 for fruit. Data were evaluated using the principal components and cluster methods obtained by UPGMA method from the similarity matrix (Euclidian mean distance), using the Genes software. By principal component analysis, it has been found that the first three components have absorbed 52.11% of the accumulated variation. The characteristics that most contributed to the discrimination of genotypes were fresh fruit weight, stigma length, length of corona filaments, fruit width, petal width and pulp weight, which are more responsive for the selection of P.cristalina genotypes. Smaller contributions to diversity were obtained from anther width, bract width and fruit length. The smallest contributions for diversity were obtained from the following characteristics: anther width, bract width and fruit length. Through UPGMA clustering method, it was found that there is a large genetic divergence among genotypes analyzed because all genotypes were grouped with over 50% of dissimilarity. This study identified genotypes 4, 5 and 9 as the most divergent and therefore the most suitable for breeding in future breeding programs and genetic conservation of the species.